An introduction to electrical engineering materials - Indulkar, C.S (S.Chand, 1990)
An introduction to electrical engineering materials / Indulkar, C.S. -- New Delhi: S.Chand, 1990 621.3 In38e3 3rd ed. No. of Copies : 1